Testing for efficiency in the Saudi stock market: does corporate governance change matter? - Mamdouh Abdulaziz Saleh Al-Faryan; Everton Dockery (Review of Quantitative Finance and Accounting, 2020)
We study the informational efficiency of the Saudi stock market (SSM), while accounting for corporate governance change, based on single, multiple, and variance ratio-based WALD tests and runs test. The main findings indicate that when the whole period is considered, the random walk hypothesis is rejected, but when divided into two sub-periods separated by the pre-corporate governance and the period marked by corporate governance change, the analysis demonstrates sub-period improvement in weak-form efficiency for the examined series. Robustness of results is verified by analysis using sector indices, which point to market efficiency. Interestingly, Hurst Exponent estimates evidence long-range dependence which suggests the predictability of stock prices and the prospect of speculative opportunities.
Keywords: G14; G15; G34; 330; Saudi stock market; Corporate governance; Market efficiency; Random walk; Variance ratio; Hurst exponent